1996
DOI: 10.1002/j.1460-2075.1996.tb00644.x
|View full text |Cite
|
Sign up to set email alerts
|

The crystal structure of the ternary complex of T.thermophilus seryl-tRNA synthetase with tRNA(Ser) and a seryl-adenylate analogue reveals a conformational switch in the active site.

Abstract: The low temperature crystal structure of the ternary complex of Thermus thermophilus seryl‐tRNA synthetase with tRNA(Ser) (GGA) and a non‐hydrolysable seryl‐adenylate analogue has been refined at 2.7 angstrom resolution. The analogue is found in both active sites of the synthetase dimer but there is only one tRNA bound across the two subunits. The motif 2 loop of the active site into which the single tRNA enters interacts within the major groove of the acceptor stem. In particular, a novel ring‐ring interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
169
1
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(188 citation statements)
references
References 36 publications
(124 reference statements)
17
169
1
1
Order By: Relevance
“…This clearly suggests that induced fit may be a major mechanism for enhancement of discrimination between cognate and noncognate tRNAs provided the conformational change gives rise to an active site with greater complimentarity to the transition state. Such a mechanism has been suggested before for other aminoacyl-tRNA synthetases (Cusack et al, 1996). We thus conclude that the binding interactions of the cognate and the noncognate tRNAs are similar.…”
Section: Discussionsupporting
confidence: 84%
“…This clearly suggests that induced fit may be a major mechanism for enhancement of discrimination between cognate and noncognate tRNAs provided the conformational change gives rise to an active site with greater complimentarity to the transition state. Such a mechanism has been suggested before for other aminoacyl-tRNA synthetases (Cusack et al, 1996). We thus conclude that the binding interactions of the cognate and the noncognate tRNAs are similar.…”
Section: Discussionsupporting
confidence: 84%
“…However, sequence alignments may suggest participation of methanogenic M. barkeri SerRS Glu-338 in discriminator base recognition. As to the bacterial enzyme, its motif 2 loop shows a great degree of similarity with the loop of T. thermophilus SerRS; therefore, it may be proposed that Glu-230 of the M. barkeri SerRS is involved in G73 recognition analogous to Glu-260 in the T. thermophilus structure (47). Unfortunately, the available data are insufficient to comment on anticodon stem recognition.…”
Section: Trnamentioning
confidence: 99%
“…2). 18,19 P. horikoshii SerRS also has additional basic residues in the region proximal to the extra arm: Arg41, Arg49, Arg51, Lys396 and Arg398. Our mutational analyses revealed that these residues indeed contribute to the tRNA recognition by P. horikoshii SerRS (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…15 Consistent with the biochemical studies, the crystal structure of the Thermus thermophilus SerRS and tRNA Ser complex clearly revealed that SerRS interacts with the first six base-pairs in the extra stem, and the first six base-pairs in the acceptor stem, but does not interact with the anticodon arm. 18,19 The crystal structure also revealed the enzyme interaction with G73 and C74.…”
Section: Introductionmentioning
confidence: 92%